Fine mapping and epistatic interactions of the vernalization gene VRN-D4 in hexaploid wheat - Kippes, Néstor Fabián; Zhu, Jie; Chen, Andrew; Vanzetti, Leonardo Sebastian; Lukaszewski, Adam; Nishida, Hidetaka; Kato, Kenji; Dvorak, Jan; Dubcovsky, Jorge (2018)
Wheat vernalization requirement is mainly controlled by the VRN1, VRN2, VRN3, and VRN4 genes. The first three have been cloned and have homoeologs in all three genomes. VRN4 has been found only in the D genome (VRN-D4) and has not been cloned. We constructed a high-density genetic map of the VRN-D4 region and mapped VRN-D4 within a 0.09 cM interval in the centromeric region of chromosome 5D. Using telocentric 5D chromosomes generated from the VRN-D4 donor Triple Dirk F, we determined that VRN-D4 is located on the short arm. The VRN-D4 candidate region is colinear with a 2.24 Mb region on Brachypodium distachyon chromosome 4, which includes 127 predicted genes. Ten of these genes have predicted roles in development but we detected no functional polymorphisms associated to VRN-D4. Two recombination events separated VRN-D4 from TaVIL-D1, the wheat homolog of Arabidopsis vernalization gene VIL1, confirming that this gene is not a candidate for VRN-D4. We detected significant interactions between VRN-D4 and other four genes controlling vernalization requirement (Vrn-A1, Vrn-B1, Vrn-D1, and Vrn-B3), which confirmed that VRN-D4 is part of the vernalization pathway and that it is either upstream or is part of the regulatory feedback loop involving VRN1, VRN2 and VRN3 genes. The precise mapping of VRN-D4 and the characterization of its interactions with other vernalization genes provide valuable information for the utilization of VRN-D4 in wheat improvement and for our current efforts to clone this vernalization gene.